КОМПЛЕКС МВПР С РАСЩЕЛИНОЙ НЕБА У РЕБЕНКА С СЕГМЕНТНОЙ МОНОСОМИЕЙ 11Q14.1Q22.1 - Румянцева, Наталья Владимировна; Гончарова, Елена Геннадьевна; Зимовина, Татьяна Сергеевна; Хурс, Ольга Михайловна; Ершова, Алла Аркадьевна (FORCIPE, 2022)